Collaborative Business Model Innovation Process for Networked Services - Marikka Heikkilä; Jukka Heikkilä (Springer, 2022)
This paper presents a process framework for innovating joint business models (co-BM) for multiple companies. Our framework describes the change management that should be carried out in parallel to the rigorous analysis and development of the business model details. With two illustrative cases we show that fruitful co-BM creation process in networks requires both development of the model itself, but also organizational innovation processes including mutual learning and harmonisation of operations. We claim that by understanding this dual process and its key facets might help (1) to coordinate the practical BM creation projects better and (2) to analyse which BM related decisions contribute or hinder the joint development project.
Co-created Effective, Agile, and Trusted eServices